Kehamilan Pasca Tindakan Manchester Fothergill - Ertandri, Yodi; Ermawati, Ermawati (Andalas Obstetrics And Gynecology Journal, 2020)
Pregnancy after a manchester fothergill action is rare, occurring 1-10,000 post-action. post- manchester fothergill pregnancy can cause premature labor, spontaneous abortion, fetal death, maternal urinary complaints, and sepsis. Case of a 34-year-old female patient, G3P1A1L1 37-38 weeks of term parturient latent phase of first stage + once previous cesarean section + history of manchester fothergill. Previous history of childbirth the patient gave birth through cesarean section and term, the birth weight of children 3200 gr. The second pregnancy the patient suffered a miscarriage at 13-14 weeks gestation and found cervical elongation, then the patient was performed cervical reconstruction with the manchester fothergill procedure after the patient received his normal menstrual cycle. after 2 years later the patient came pregnant with a gestational age of 9 months with complaints of low back pain in the placenta. The conclusion of this case of pregnancy after the manchester fothergill action is a rare condition. pelvic organ prolapse and cervical elongation in pregnancy are conditions to be aware of, therefore early diagnosis is very important for smooth pregnancy. individual approach depends on gestational age, the severity of the prolapse is a matter that must be considered for the choice of delivery. prevention of complications can determine the success of a pregnancy. it must also be concluded that prolapse is not a disease of the elderly. Keywords: cervical elongation, Manchester Fothergill